Energy Efficiency Services Limited (EESL) : shaping the industry - Maheshwari, Sunil Kumar, (SAGE business cases., 2020)
Saurabh Kumar, the Managing Director (MD) of Energy Efficiency Services Limited (EESL) was happy as he glanced through the financial results of the company. EESL had earned attractive profits. The company had led the consolidation and transformation of the electric lighting industry that had facilitated energy efficiency in the country, in a very short period. The company had distributed more than 365 million LED bulbs in the country by the end of the year 2020. It was truly a proud moment for the entire management team of EESL. Yet Kumar was not content. His vision was to reach INR 100 billion in revenues by 2025. He called for a meeting of his top management team to decide the future course of action.